Protective Effects of Bariatric Surgery on Kidney Functions by Inhibiting Oxidative Stress Responses Through Activating PPARα in Rats With Diabetes - Jiang, Hong-Wei; Zhou, Yong; Zhou, Pin-Yi; Zhang, Tian-Yi; Hu, Jing-Yao; Bai, Xue-Tao (Frontiers in Physiology, 2021)
Objective The aim of this study was to explore the protective effects and the regulatory mechanisms of bariatric surgery on kidney injury in diabetic rats. Methods We established a useful type 2 diabetic rat model using high-fat and high-sugar diet feeding following low-dose streptozotocin (STZ) treatment. Sprague–Dawley (SD) rats were randomly divided into the following groups: control (Con) group, diabetic nephropathy (DN) group, and duodenal–jejunal bypass (DJB) surgery group. The food intake and body weight of rats were monitored and the glucose tolerance test (OGTT) test was performed every 2 weeks. The glomerular filtration rate (GFR) and urinary albumin excretion rate (UAFR) were measured to assess renal function. Hematoxylin–eosin (H&E), periodic acid–Schiff (PAS), and Masson staining were used to evaluate renal histopathological changes. TUNEL assay was performed to detect cell apoptosis. The expressions of oxidative stress factors and inflammatory factors in the renal tissues of rats were detected by ELISA. The expressions of PPARα, reactive oxygen species (ROS), and NF-κB were detected by immunofluorescence. For in vitro experiment, HK2 cells cultured with high glucose were treated with PPARα agonist, PPARα antagonist, and adenosine 5′-monophosphate (AMP)-activated protein kinase (AMPK) agonist. The expressions of AMPK/PPARα/NF-κB signaling pathway-related proteins were detected by Western blot. Results Bariatric surgery improved the glucose tolerance of DN rats. The GFR was decreased, the promotion of urinary albumin excretion rate (UAER) was inhibited, and the renal injury was alleviated. The extracellular matrix fraction was decreased and the renal function was improved. Meanwhile, bariatric surgery activates PPARα, inhibits ROS release, reduces oxidative stress injury, and reduces renal cell apoptosis. In vitro experiment results showed that the AMPK activator could activate PPARα, downregulate NF-κB, and inhibit inflammatory response. The phosphorylation of AMPK was inhibited by PPARα antagonism. Conclusion Bariatric surgery can activate PPARα, inhibit oxidative stress injury, and improve glucose metabolism and renal function in DN rats.